(3JShjI efGRYGJ YbhO GSJZdGd GdKQhGJ GdWHjYjI (B:s (3JWHjbGJ ef NdGd GdeQcR GdOhdj dJShjI efGRYGJ GdGSJKeGQ (B/s - (3YHOGddg SYjO YHOGddg GdHQhGQjs; (3LGHQ LGO fUGQs; (3LGeYI GdOhd GdYQHjIs (3eYgO GdHMhK hGdOQGSGJ GdYQHjIs ((3GdbGgQI(B:s (3eYgO GdHMhK hGdOQGSGJ GdYQHjI(B- (3LGeYI GdOhd GdYQHjI,s, 2014)
(3GfWdGbG ef MbjbI Cf eaghe GSJZdGd GdKQhGJ GdWHjYjI jJYOi ZGjJfg GdCSGSjI GdCbJUGOjI djchf JYHjQ GYf eOi GSJbdGd SjGOI OhdI eG cQcf GSGSi dhLhOgG HGdeaghe GdMOjK ef NdGd SjGOJgG Ydi KQhGJgG GdWHjYjIs
(3QSGFd fSNI efaQOIs
(3jTJed Ydi edGMbs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdOhd GdYQHjI, eYgO GdHMhK hGdOQGSGJ GdYQHjI, bSe GdOQGSGJ GdbGfhfjI (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B527- 575s
Keywords: (3GdbGfhf GdEOGQjs; (3GdeTQY GdYQGbjs; (3SdWI GdQbGHIs; (3SdWI GdJaJjTs; (3SdWI JhbjY GdLRGAGJs; (3eSGFd GdGNJUGUs; (3GdbVGA GdeOfj GdaQfSjs; (3eMceI GdJfGRY GdaQfSjIs; (3GdGNJUGU GdQVGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdOhd GdYQHjIs